Archilochus, 196a IEG2 - Schade, Gerson (Hyperboreus, 2015)
In the history of European literature, Archilochus is the ﬁrst poet whose individuality can be discerned. His proliﬁc output provided many an opportunity to create a literary persona, somehow not completely independent from the author’s personality. Since his earliest readers this literary project of his did not pass unnoticed, and Archilochus’ works were read as autobiographical statements or reduced to such. The reception of the so-called Cologne Epode, where the temptation to see something biographical was for many irresistible, is no exception to the rule.Instead the proposed new commentary offers another approach: the text is judged on its own, put in perspective, and annotated in a way that informs experienced students from different backgrounds about its speciﬁc, Archilochean aspects. Archaeological evidence and literary imitation are referred to, technical terms relating to classical studies not avoided, yet not used excessively. Thus focusing on selected, important issues as, for instance, textual interplay, the commentary helps to assess Archilochus’ considerable literary merits.